2019
DOI: 10.20964/2019.06.62
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Titanium Electrodes in the Alternating Polarity Electrolysis

Abstract: Electrolysis of water performed by microsecond voltage pulses of alternating polarity has been used to generate nanobubbles in microscopic systems. These nanobubbles exhibit interesting and useful effects, but their production requires a high current density of >10 A/cm 2. Deposited platinum or gold electrodes cannot withstand these conditions for a long time. Titanium showed the best durability, although it also undergoes degradation. The mechanism of degradation differs from that in usual DC electrolysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…It was concluded that Pt electrodes are destroyed mechanically by a local energy deposition due to the reaction between NBs near the electrode surface. Investigation of Ti electrodes revealed different mechanism of the degradation 37 . In this case the growth of titanium oxide on the electrode surface is responsible for the reduction of the Faraday current during the first minute of the AP process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that Pt electrodes are destroyed mechanically by a local energy deposition due to the reaction between NBs near the electrode surface. Investigation of Ti electrodes revealed different mechanism of the degradation 37 . In this case the growth of titanium oxide on the electrode surface is responsible for the reduction of the Faraday current during the first minute of the AP process.…”
Section: Resultsmentioning
confidence: 99%
“…On one side, the energy deposition from exploding NBs provides significant local stresses 10 , 36 on chemically inert electrodes such as Pt. On the other side, harder materials are oxidised resulting in the reduction of the current 37 as it occurs for Ti.…”
Section: Introductionmentioning
confidence: 99%
“…One has to note that for Ti electrodes the average current per pulse is reduced during a few minutes but then reaches a steady state. A special investigation [30] showed that the current decrease is related to growth of titanium oxide layer and during this growth there is disbalance between oxidation and reduction processes. Finally, the balance is reached due to presence of cracks and pores in the oxide layer.…”
Section: Resultsmentioning
confidence: 99%
“…To Previous work has shown that exposing electrodes to a conductive solution at low frequencies can cause electrode degradation. 54,55 Seen in Figure 4.1, even after many uses at a high frequency, the electrodes in Figure 4.1C have not degraded to the degree of the electrodes in When compared to the new electrodes in Figure 4.1A, the used electrodes have also degraded, though this is expected after multiple uses at high voltages and frequencies. Thus, radio frequency current provides the least electrode degradation and is the preferred frequency range for E-NAAMP.…”
Section: Frequency Effect On Electrode Integritymentioning
confidence: 89%